(untitled) (Journal of Technology Research, 2025)
Libya’s current recovery plans hinge on maximising value from existing crude streams without the luxury of massive capital expenditure. In this context, a precise understanding of how Libyan crudes differ in their physical and chemical personalities is no longer academic—it is an operational necessity. We present an integrated laboratory campaign that captures three geographically distinct crude arteries (Brega, Nafoora, and Bouri) and subjects them to the most current ASTM/IP protocols for density, viscosity, pour point, flash point, elemental (C/H/S) analysis, metals (Ni, V), and asphaltene quantification. .Brega emerges as an exceptionally light (42.4 ° API), sweet (0.9 wt % S) and low-metal crude. Its quality makes it an excellent candidate for simple refining configurations like topping units, or as a premium feed for FCC gasoline production after distillation. Bouri sits at the opposite corner of the matrix: heavy (25.8 °API), sour (1.86 wt% S), and asphaltene-rich (21.3 wt%). Nafoora occupies the middle ground, inviting a selective hydro-treating route. Beyond the numbers, we reconcile the data with the underlying geology and offer pragmatic guidelines for blending, desalter design, pipeline hydraulics, and refinery revamps. The dataset is provided in full as electronic supplementary material to enable independent verification and future modelling work.